2021
DOI: 10.1088/1755-1315/810/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Probiotic from Hymenachne Acutigluma Silage in Feed to the Length of Small Intestine and Caeca in Pegagan Ducks

Abstract: This study aims to determine the effect of giving probiotics from (hymenachne acutigluma) silage in feed to the length of smallintestine and caeca in Pegagan ducks. The object of this research is sixty 5 months Pegagan ducks. The research design used was a Completely Randomized Design (CRD) with 5 treatments and 4 replications. There is 3 Pegagan ducks as a variable unit: P0 (Control); P1 (Ration + Probiotics with a dose 0,2%); P2 (Ration + Probiotics with a dose 0.4%); P3 (Ration + Probiotics with a dose 0.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…(Kheravii et al, 2017). Additional, giving probiotics from Kumpai Tembaga grass silage into the ration at a dose of 0.2% was able to increase the percentage of small intestinal (Sandi et al, 2021). Some research revealed that fiber functions as prebiotics in the large intestine and ceca and may help the chicks' gastrointestinal system choose a healthy microbiome (Teng and Kim, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(Kheravii et al, 2017). Additional, giving probiotics from Kumpai Tembaga grass silage into the ration at a dose of 0.2% was able to increase the percentage of small intestinal (Sandi et al, 2021). Some research revealed that fiber functions as prebiotics in the large intestine and ceca and may help the chicks' gastrointestinal system choose a healthy microbiome (Teng and Kim, 2018).…”
Section: Discussionmentioning
confidence: 99%